Interval between two-stage exchanges: what is optimal and how do you know? - Ricardo Sousa; André Carvalho; Daniel Soares; Miguel Araújo Abreu (Arthroplasty, 2023)
Abstract Background Two-stage exchange arthroplasty remains the most popular option for the treatment of chronic periprosthetic joint infection (PJI). Determining infection eradication and optimal timing of reimplantation can be challenging. Information to allow for a truly informed evidence-based decision is scarce. Methods We conducted a critical review of available evidence on the presently available tests to help determine timing of reimplantation. Results Serology is traditionally used to follow up patients after the first stage. Despite tradition mandates waiting for normal inflammatory markers, there is actually no evidence that they correlate with persistent infection. The role of synovial fluid investigation between stages is also explored. Cultures lack sensitivity and neither differential leukocyte counts nor alternative biomarkers have proven to be accurate in identifying persistent infection with a spacer in situ. We also examined the evidence regarding the optimal time interval between resection and reimplantation and whether there is evidence to support the implementation of a two week “antibiotic holiday” prior to proceeding with reimplantation. Finally, wound healing and other important factors in this setting will be discussed. Conclusion Currently there are no accurate metrics to aid in the decision on the optimal timing for reimplantation. Decision must therefore rely on the resolution of clinical signs and down trending serological and synovial markers.